Types and Size Distribution of Parrotfish (Family Scaridae) Caught with Gillnets in the Waters off Taduna Village, Kabaruan Island. - Rumping, Agustiani M. V.; Rondonuwu, Ari B.; Kondoy, Khristin F I.; Lalita, Jans Djoike; Rangan, Jetty K.; Tombokan, Leonard J. (Jurnal Ilmiah Platax, 2023)
The objective of this research is to identify the types and size distribution of parrotfish in the waters of Taduna Village. The research was conducted using sampling methods. Samples were collected over a period of two months from the catches landed in Taduna Village by local fishermen. The fishermen used gillnets for their catches. The length of each fish was measured from the tip of the mouth to the end of the tail using a millimeter-scale ruler with a precision of 0.1 cm. The weight of the fish was measured using a digital scale with a resolution of one gram. The length of each species was analyzed using frequency distribution and presented in length and weight histograms. Based on the data obtained from the measurements of Family Scaridae fish, a total of 53 individuals were collected, consisting of 8 species: Chorurus bleekeri (11 individuals), Calotomus carolinus (4 individuals), Chorurus japanensis (6 individuals), Chlorurus microrhinos (2 individuals), Scarus frenatus (16 individuals), Scarus russell (4 individuals), Scarus spinus (5 individuals), and Scarus tricolor (5 individuals). The distribution of Family Scaridae fish in the waters off Taduna Village shows varying lengths and weights for each species. For example, Chorurus bleekeri ranged from 18.9 to 26.5 cm in length and weighed between 150 and 394 grams, Chorurus japanensis had a length distribution between 17.5 and 27.4 cm and weighed from 119 to 465 grams, and Scarus frenatus ranged from 18.3 to 24.5 cm in length and weighed between 117 and 308 grams." Keywords: Parrotfish, Scaridae, Types, Size, Kabaruan. Abstrak Tujuan penelitian ini yaitu untuk mengetahui jenis dan distribusi ukuran ikan kakatua di perairan Desa Taduna. Penelitian ini menggunakan metode sampling. Pengambilan sampel dilakukan dalam waktu dua bulan dari hasil tangkapan nelayan yang didaratkan di Desa Taduna. Alat yang digunakan nelayan adalah jaring insang mono filamen. Seluruh panjang ikan diukur dari ujung mulut hingga ujung ekor dengan penggaris skala milimeter dengan ketelitian 0,1 cm. Berat ikan diukur dengan timbangan digital dengan resolusi satu gram. Panjang setiap spesies dianalisis menggunakan distribusi frekuensi dan ditampilkan dalam histogram panjang dan berat. Berdasarkan data hasil pengukuran ikan Famili Scaridae diperoleh sebanyak 53 individu yang terdiri dari 8 spesies yaitu Chorurus bleekeri (11 individu), Calotomus carolinus (4 individu), Chorurus japanensis (6 individu), Chlorurus microrhinos (2 individu), Scarus frenatus (16 individu), Scarus russellii (4 individu), Scarus spinus (5 individu) dan Scarus tricolor (5 individu). Distribusi ikan Famili Scaridae di perairan depan Desa Taduna memiliki ukuran panjang dan berat yang bervariasi yaitu spesies Chorurus bleekeri berkisar 18,9-26,5 cm dan berat 150-394 gram, Chorurus japanensis memiliki distribusi ukuran panjang berkisar 17,5-27,4 cm dan berat 119-465 gram dan Scarus frenatus memiliki distribusi ukuran panjang berkisar 18,3-24,5 cm dan berat 117-308 gram. Kata kunci : Ikan kakatua, Scaridae, Jenis, Ukuran, Kabaruan